INTERROGATIVE SENTENCE IN MINANGKABAU LANGUAGE: X-BAR THEORY - Dian Zelina Fitriyani (RETORIKA: Jurnal Ilmu Bahasa, 2017)
This study discusses the grammatical function of the question words and the internal structure of interrogative sentence in Minangkabau language. The study of this interrogative sentence structure applies X-bar theory as one of the generative syntax subtheories. The data is gained from the interview of Minangkabau language native speaker and analysed by using the distributional method. The result of the analysis shows that the question words for wh-question has two grammatical functions, specifier and complement. For yes-no question, the question word â€œiyonyoâ€ has one grammatical function, that is complement. The internal structure of interrogative sentence in Minangkabau language is constructed by specifier, complement, and adverb. Key words: interrogative sentence, question word, Minangkabau language